Effect of Microalloyed Elements M (M = Ce, Ti, V, and Nb) on Mechanical Properties and Electronic Structures of γ‐Fe: Insights from a First‐Principles Study. Issue 9 (6th May 2021) - Liu, Xiangjun; Yang, Jichun; Cai, Changkun; Li, Anxin; Lei, Xiao; Yang, Changqiao
Abstract : Herein, the first‐principles calculation is used to study the solid solution behavior of microalloyed elements M (M = Ce, Ti, V, and Nb) in steel, and the effects of M on the mechanical properties and electronic structures of the doped systems are analyzed. The calculated results of the solvation energy and formation enthalpy show that Ce, Ti, V, and Nb can be solubilized in γ‐Fe. The elastic modulus calculated results show that M doped reduces the incompressibility and rigidity and of the doped system, but the toughness and machinability are improved. A combination of Bader charge and differential charge density analysis shows that the metallic bond strength of the Fe–M system is weaker than that of the pure Fe system, which is the main reason for the decrease in incompressibility and rigidity of the doped system; the higher electron cloud density of the doped system is the main reason for its toughness increase. Abstract : The first‐principles calculation method is used to study the solid solution behavior of the microalloying elements Ce, Ti, V, and Nb in steel. Ce, Ti, V, and Nb can be solubilized in γ‐Fe. Doping with these microalloying elements reduces the incompressibility and rigidity and of the system, but improves the toughness and machinability.